Drug use among university students: Consumption profile and association with parental educational level (Research, Society and Development, 2025)
Drugs of abuse can alter mood, perception, and individual functioning, leading to dependence and withdrawal syndrome. In Spain, illegal drug use remains a public health issue, especially among young people. Socioeconomic factors, such as parental educational level, may influence consumption behaviors. To analyze drug consumption among university students and its relationship with age, sex, and parental educational level. Observational, descriptive, cross-sectional study conducted among university students. A health survey was applied to assess substance use and sociodemographic data. IBM-SPSS-25 was used for statistical analysis. A total of 498 students were included (median age: 19 years; 68.7% female). 23% reported drug use, with marijuana being the most frequently consumed substance (54.5%). Significant differences were found in marijuana and hashish consumption by sex, with higher prevalence among males (p